Computed Tomography Imaging of the Coronary Arteries: State of the Art Applications and Recent Patents - Schaffer, Alon; Cassetti, Ettore; G. Di Iovine, Maria; Barbieri, Lucia; Rognoni, Andrea; G. Secco, Gioel; Lazzero, Maurizio; S. Bongo, Angelo; Porto, Italo; Lupi, Alessandro (Recent Patents on Medical Imaging (Discontinued), 2014)
Computed tomography (CT) is important for the management of many medical illnesses, including coronary artery disease (CAD). However this technique is not free from disadvantages like the exposure to ionizing radiations and to iodinated contrast agents. To overcome these problems, imaging technologies are changing rapidly. New- generation computed tomography scanners (NGCCT) may bring substantial advantages over traditional CT and other currently used imaging methods. These novel tools employ dedicated protocols to shorten imaging times and reduce radiation doses without affecting accuracy. Current CT scanners can very accurately identify severe CAD requiring intervention in most patients, but NGCCT may further benefit imaging for some “difficult” patients like obese patients, patients with high or irregular heart rates, and patients who have high coronary calcium burden or previous stents or bypass grafts. In fact in these patients traditional CT studies often produce suboptimal quality images. Our review presents the current status in the technical background of coronary nuclear tomographic imaging in the areas of clinical practice, and focuses on future developments of related patent forms.
Keywords: iodinated contrast medium